Enhancing Occupational Therapy Interventions by Integrating the Multiphase Optimization Strategy Framework. - Rosenfeld, Meirav; Goverover, Yael; Guastaferro, Kate (American Journal of Occupational Therapy)
As occupational therapy research advances and the body of evidence supporting effective interventions continues to grow, there is a need to expedite the transfer of research findings into practice, and the use of intervention development frameworks becomes increasingly essential. In this column, we introduce the Multiphase Optimization Strategy (MOST), an engineering-inspired framework for the development, optimization, and evaluation of multicomponent interventions. MOST allows for the systematic development and evaluation of optimized interventions that prioritize effectiveness within constraints like affordability, scalability, and efficiency. Using MOST while developing an intervention may reduce the delay between intervention development and real-world implementation. Moreover, adopting MOST will bolster the use of rigorous research designs in occupational therapy studies and foster shared terminology with other disciplines that have successfully applied this framework across a range of health priorities and conditions. Thus, we advocate integrating MOST into occupational therapy intervention development research. This The Issue Is column introduces the Multiphase Optimization Strategy (MOST), an engineering-inspired framework for the development, optimization, and evaluation of multicomponent occupational therapy interventions.